2012
DOI: 10.1007/s00300-011-1145-4
|View full text |Cite
|
Sign up to set email alerts
|

State-dependent incubation behaviour in the high arctic barnacle geese

Abstract: Energetic trade-offs between time spent on incubation and times spent on foraging for nesting birds give individuals in good body condition the possibility to incubate more continuously. In the present paper, the incubation behaviour of female barnacle geese Branta leucopsis was quantified in a colony in Svalbard. Females were weighted in early incubation and feeding recess lengths and frequencies were recorded. The feeding behaviour during the course of incubation was significantly correlated to by body mass,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
0
10
1
Order By: Relevance
“…Eichhorn and Karagicheva (2008) observed 42 barnacle goose nests in Arctic Russia during bouts of 6-48 h in all periods of the day and incubation stages and found a daily recess time of 157 min. Thus, our measurement falls within the measurement of Eichhorn and Karagicheva (2008) but not within the measurement of Tombre et al (2012). This is possible due to differences in methodology, measurement period and/or year differences.…”
Section: Wildlife Camera Observationscontrasting
confidence: 48%
See 1 more Smart Citation
“…Eichhorn and Karagicheva (2008) observed 42 barnacle goose nests in Arctic Russia during bouts of 6-48 h in all periods of the day and incubation stages and found a daily recess time of 157 min. Thus, our measurement falls within the measurement of Eichhorn and Karagicheva (2008) but not within the measurement of Tombre et al (2012). This is possible due to differences in methodology, measurement period and/or year differences.…”
Section: Wildlife Camera Observationscontrasting
confidence: 48%
“…Based on our data, we calculated that the time a goose was absent was on average 157.1 min (SE = 15.9) per nest per day. Tombre et al (2012) studied incubation behaviour in the same population and observed, during four 24-h cycles of 18 nests, an average recess length of 19.8 (SE = 1.2) min and a daily average number of recesses of 4.9 (SE = 0.5), which would on average give a daily recess time of 97.02 min. Eichhorn and Karagicheva (2008) observed 42 barnacle goose nests in Arctic Russia during bouts of 6-48 h in all periods of the day and incubation stages and found a daily recess time of 157 min.…”
Section: Wildlife Camera Observationsmentioning
confidence: 99%
“…Incubation breaks occurring independent of observer nest visits were most common during the warmest period of the day, and the probability of a non‐observer break was higher on days with warmer temperatures. Such patterns are frequently observed among nesting waterfowl, and may be attributed to minimizing the cooling of eggs or reducing exposure of unattended nests to predators (Thompson and Raveling , Flint and Grand , Tombre et al ). Photographs of foxes at nests were relatively more common during low‐light hours associated with the coolest portions of the day and highest rates of nest attentiveness, whereas peaks in the frequency of avian predators corresponded with the warmest period of the day and peak timing of incubation breaks.…”
Section: Discussionmentioning
confidence: 99%
“…Solid lines depict year-specific average ambient temperature during the nesting period (7 Jun-13 Jul). Raveling 1987, Flint and Grand 1999, Tombre et al 2012). Photographs of foxes at nests were relatively more common during low-light hours associated with the coolest portions of the day and highest rates of nest attentiveness, whereas peaks in the frequency of avian predators corresponded with the warmest period of the day and peak timing of incubation breaks.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, age‐related improvements in foraging and breeding skills are also associated with greater nestling performance. For example, older birds often breed on higher quality sites than younger ones (Greenwood and Harvey ), Greenwood and Harvey a large contributing factor to reproductive success (Pärt ), and nestling survival can be influenced by age‐related and condition‐dependent incubation patterns (Bogdanova et al , Tombre et al ).…”
mentioning
confidence: 99%